2018
DOI: 10.18203/2319-2003.ijbcp20185160
|View full text |Cite
|
Sign up to set email alerts
|

KAP on antibiotic usage and resistance among second professional medical students

Abstract: Background: Antibiotics are wonder drugs as they prevent and treat bacterial infections. However, their irrational use even by wrong prescribing behaviour of physician leads to antibiotic resistance medical students are future doctors and are provided knowledge and practice of antibiotics in treatment, and prevention of diseases in their study curriculum of second professional course mainly in chapters of pharmacology and microbiology. Therefore, the present study was to determine the second-year medical stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…The results on practice of antibiotics were mixed as 69.4% said they discarded the leftover medicine while on the other hand 38.8% said they save the leftover antibiotics. Number of authors have reported adequate knowledge on antibiotics use however the attitude and practice regarding antibiotic use was inadequate which is in concurrence to the results of this study [16,23]. The knowledge, attitude and practice level of first year students was lower compared to second and third year students.…”
Section: Discussionsupporting
confidence: 89%
“…The results on practice of antibiotics were mixed as 69.4% said they discarded the leftover medicine while on the other hand 38.8% said they save the leftover antibiotics. Number of authors have reported adequate knowledge on antibiotics use however the attitude and practice regarding antibiotic use was inadequate which is in concurrence to the results of this study [16,23]. The knowledge, attitude and practice level of first year students was lower compared to second and third year students.…”
Section: Discussionsupporting
confidence: 89%
“…In the same year, Al-Salih and colleagues, after conducting a study about knowledge and attitude regarding antibiotic use among nursing and dentistry students in Babylon University (Iraq), have concluded that despite their knowledge about the appropriate antibiotic use, students lacked in the appropriate attitude [11]. The same conclusion has been reached regarding professional Indian medical students by Khajuria and colleagues in 2018 [12]. A crosssectional questionnaire based study conducted among 2500 Chinese students regarding their KAP of antibiotics concluded that the medical curriculum improves the students' knowledge on antibiotics.…”
Section: Introductionmentioning
confidence: 76%
“…On the other hand, Jairoun and his colleagues have reported in 2019 that the large majority of university students were aware that antibiotics can kill bacteria and can be used to cure bacterial infections [8]. Moreover, Khajuria et al 2019 showed that 90% of medical students agreed that antibiotics are useful for bacterial infections [12]. Gary and colleagues, have reported in 2012, while comparing the KAP related to antibiotic use and resistance among medical and non-medical university students in Jordan, that 44% percent of non-medical students and 28.1% of medical students agreed that antibiotics could cure cold and viral infections [23].…”
Section: Discussionmentioning
confidence: 99%
“…22 Abuse of antibiotics has been reported by many other researchers as one of the main factors leading to antibiotic resistance. 4,24,28,34 Regarding the necessity to get more education about antibiotics and antibiotic resistance, 95.8% of the participants in our study agreed that it was necessary. Further, 76.9% of the participants in our study agreed that education on the rational use of antibiotics is very cardinal.…”
Section: Knowledge Of Participants Of Antibiotic Use and Resistancementioning
confidence: 84%
“…27 Khajuria et al in India similarly reported that 90% of the medical students knew the indication of antibiotics. 28 The reason for this could be because participants might have come across this topic in medical microbiology, pharmacology, and practicals for clinical students.…”
Section: Knowledge Of Participants Of Antibiotic Use and Resistancementioning
confidence: 99%